Mengintegrasikan Pluralisme dan Multikultural dalam Pengembangan Manajemen Sumber Daya Manusia (MSDM) - Darwin Nasution; Muhlisah Lubis (Jurnal Simki Economic, 2026)
This article discusses the importance of integrating pluralism and multiculturalism in Human Resource Management (HRM) development as a response to the challenges of globalization and diversity in the workplace. Pluralism and multiculturalism are not only social concepts but also strategic approaches that can improve organizational effectiveness through understanding and respecting differences in culture, religion, values, and outlooks. This research highlights how a pluralism-based approach can create an inclusive work environment, increase productivity, and strengthen collaboration among individuals with diverse backgrounds. Furthermore, this article identifies best practices for integrating multicultural principles into HRM policies, such as employee recruitment, training and development, and conflict resolution. With this approach, organizations can not only meet the demands of diversity but also leverage it as a competitive advantage. This article concludes that developing HRM based on pluralism and multiculturalism is a crucial step in creating sustainability and harmony in an increasingly complex and heterogeneous workplace.